2004
DOI: 10.1128/jvi.78.4.2158-2163.2004
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analyses of Texas Isolates Indicate an Evolving Subtype of the Clade B Feline Immunodeficiency Viruses

Abstract: Rigorous phylogenetic analyses were used to compare the nucleotide sequences of feline immunodeficiency virus strains isolated from Texas and throughout the world. The envelope V3-V4 sequences and capsid gene of the Texas isolates formed a cluster between subtypes B and E. Statistical comparisons with other published sequences confirmed that the Texas group is a unique cluster, possibly a new subtype, arising from subtype B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 29 publications
2
25
0
3
Order By: Relevance
“…Five distinct FIV subtypes have been identified, based on sequence diversity within the V3 to V5 region of the envelope gene (13,20,29). A recent study identified a distinct group of FIV isolates from Texas that possibly represent a new subtype (32). In addition, intersubtype recombination has been detected in natural populations (1,4,23).…”
mentioning
confidence: 99%
“…Five distinct FIV subtypes have been identified, based on sequence diversity within the V3 to V5 region of the envelope gene (13,20,29). A recent study identified a distinct group of FIV isolates from Texas that possibly represent a new subtype (32). In addition, intersubtype recombination has been detected in natural populations (1,4,23).…”
mentioning
confidence: 99%
“…On the basis of the analysis of envelope glycoprotein variable regions 3-5, FIV has been classified into five subtypes [17], [27,35], a number that can be expected to increase as further studies reveal additional diversity. Recent studies identified distinct groups of FIV isolates from the Unites States and New Zealand [40,10]. Although genetic subtyping, in general, is based on nucleotide sequences from gag [4], [12], the high varia bility of the lentiviral env gene makes it the preferred region for subtyping [18].…”
mentioning
confidence: 99%
“…Como observado neste trabalho, a existência de subgrupos dentro do subtipo B já havia sido descrita (Steinrigl & Klein 2003, Weaver et al 2004, inclusive no Brasil (Caxito et al 2006). A maior implicação para a formação de subgrupos dentro de um subtipo consiste na dificuldade de se utilizar diagnóstico baseado em biologia molecular (Steinrigl & Klein 2003).…”
Section: Resul Resul Resul Resul Results T T T Tados E Discus Ados E Dunclassified
“…Os subtipos A e B têm sido os mais freqüentemente identificados (Duarte & Tavares 2005) e estudos recentes demonstraram a ocorrência de subgrupos dentro do subtipo B (Steinrigl & Klein 2003, Weaver et al 2004, Duarte & Tavares 2005, refletindo a diversidade genética observada nos diferentes subtipos do FIV (Sodora et al 1994, Bachmann et al 1997.…”
unclassified